Have Teachers Conducted Collaborative Assessment in Elementary Schools? - Mutiah, Ulin Nuskhi; Makin, M; Yuliatun, Y (Proceedings International Conference on Education Innovation and Social Science, 2023)
Collaborative skills and critical thinking, creative and communication skills are mandatory in the 21st century. Collaborative abilities can be enhanced by providing practical learning and assessment in schools. After implementing the 2013 curriculum in Indonesia, the government provided collaborative assessment through the teacher's book. However, its implementation in the field has not been optimal and still encounters various obstacles. This study aims to describe the implementation of collaborative assessment in elementary schools in the Province of DIY Indonesia. This research is qualitative research with a phenomenological approach. Data was collected through interviews and observations involving 10 participants, namely elementary school teachers in the province of DIY Indonesia. Data analysis uses Milles & Huberman with the stages of data collection, display, condensation, and conclusion. The research results show that the teacher's assessment of collaboration skills comes from the results of group work accompanied by presentation skills. The statement that the assessment was carried out based on the rubric provided in the teacher's book, but it was found that there were still teachers who did not understand how to compose the correct cooperative assessment instrument, as well as the difficulty in assessing students one by one during the learning process also caused collaborative assessment in schools not to be carried out.